GEOGRAPHICAL FEATURES AND AUTHENTIC CULTURE AS ATTRACTIONS OF VISCRI COMMUNITY-BASED TOURISM IN ROMANIA - Mihai Voda; Saroun Sok; Noeline Nakanjakko; Denis Mwanje; Ni Made Ernawati (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2018)
This article aims at presenting a discussion on Viscri tourist attractions in Romania which could add to the existing discourse on Viscri community-based tourism (CBT) and could become an input for the community members and other stakeholders of the CBT site. Using the cultural and natural heritage provides Viscri CBT site with a strong base for its tourist attractions. Nonetheless, using authentic culture as tourist attraction creates a paradox; the community-based tourism site is expected to keep its originality while development is the aim to be achieved by the tourism development project. This issue needs to be tackled by Viscri management for the sustainability of Viscri as a community and tourist site. Some efforts have been undertaken in terms of physical structures, which could be followed by other members of the community. A more comprehensive and well-planned step is required and it should be communicated to the people on how the paradox is resolved.